2020
DOI: 10.1029/2020gl088651
|View full text |Cite
|
Sign up to set email alerts
|

Using a Deep Neural Network and Transfer Learning to Bridge Scales for Seismic Phase Picking

Abstract: The important task of tracking seismic activity requires both sensitive detection and accurate earthquake location. Approximate earthquake locations can be estimated promptly and automatically; however, accurate locations depend on precise seismic phase picking, which is a laborious and time‐consuming task. We adapted a deep neural network (DNN) phase picker trained on local seismic data to mesoscale hydraulic fracturing experiments. We designed a novel workflow, transfer learning‐aided double‐difference tomog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 27 publications
(56 reference statements)
0
46
0
Order By: Relevance
“…The phyllitic rock mass with strong foliation planes and ubiquitous fractures does however show anisotropic velocity behavior as well as lateral heterogeneity. In order to characterize the heterogeneity, Chai et al (2020) built on our analysis of the seismic events and applied the PhaseNet software (Zhu & Beroza, 2019) and transfer learning to measure additional arrival times and performed a 3‐D tomographic study using the tomoDD package (Zhang & Thurber, 2003). While their relative relocations provide some higher‐resolution images of the identified fractures, the differences to the absolute locations presented here are fairly minor.…”
Section: Discussionmentioning
confidence: 99%
“…The phyllitic rock mass with strong foliation planes and ubiquitous fractures does however show anisotropic velocity behavior as well as lateral heterogeneity. In order to characterize the heterogeneity, Chai et al (2020) built on our analysis of the seismic events and applied the PhaseNet software (Zhu & Beroza, 2019) and transfer learning to measure additional arrival times and performed a 3‐D tomographic study using the tomoDD package (Zhang & Thurber, 2003). While their relative relocations provide some higher‐resolution images of the identified fractures, the differences to the absolute locations presented here are fairly minor.…”
Section: Discussionmentioning
confidence: 99%
“…Their study showed that CNN in combination with RNN is more promising for P-and S-detection when there are not enough training data available. To mitigate high intensive labour and thus high cost of manual seismic picking, the study [30] transferred the PhaseNet model and incorporate it with double-difference tomography. The results showed that the model's prediction was nearly as accurate as the result of a human expert with very low time and cost.…”
Section: Related Workmentioning
confidence: 99%
“…However, additional seismic events could be located close to the injection interval. These were relocated by Chai et al (2020) using tomoDD for joint inversion for relative locations and a 3-D velocity model. Figure 4 shows the seismicity located during the entire test together with our absolute location of the discrete shear event.…”
Section: Early Shear Eventmentioning
confidence: 99%
“…The slip vectors also coincide with the plane defined by the machined notch, indicating that it could have helped to initiate the slip event. (Chai et al, 2020) with an average plane and slip vectors for the shear event measured by the SIMFIP.…”
Section: Early Shear Eventmentioning
confidence: 99%
See 1 more Smart Citation